Effect of Several Types of Compost on The Growth and Yield of Rice - Budi Santosa; Muhammad Amri; Yurma Metri; Desi Ratna Sari (Agrotechnology Research Journal, 2025)
Compost is an organic fertilizer produced through the decomposition of plant residues, animal waste, and other organic materials, playing a vital role in enhancing soil fertility, nutrient availability, and microbial activity. This study aimed to evaluate the effectiveness of various compost types on the growth and yield of rice. The experiment was conducted in Nagari Koto Baru, Solok Regency, from July to December 2022, using a Randomized Block Design (RBD) with six treatments of compost type and four replications: no compost, kirinyuh (Chromolaena odorata), rice straw, grass, corn leaf, and cow dung compost. The dose of compost used in all treatments was the same, at 100 g per pot. Composting was carried out for 30 days, utilizing PROMI microorganisms to accelerate decomposition. Data were analyzed using analysis of variance and Duncan’s New Multiple Range Test at a 5% significance level. The results indicated that kirinyuh compost produced the best response across all observed parameters, including plant height (76.20 cm), number of leaves (79.80), number of tillers (30.50), nmber of productive tillers (28.00), panicle length (26.00 cm), number of grains per panicle (170.00), weight of 1,000 grains (28.00 g), and grain weight per pot (105.00 g). This yield corresponds to a potential production of 9.45 t.ha-1. These findings highlight Kirinyuh compost as a promising local organic fertilizer capable of sustainably increasing rice productivity while improving soil health.